THE ROLE OF MUI, HALAL CENTER, AND SUPPORTING FACTORS IN ENHANCING THE SUCCESS OF HALAL PRODUCT CERTIFICATION FOR NTB MSME’S - Mariana,; Tondoyekti, Kukuh; Kamala Hady, Lalu (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study investigates the influence of the Indonesian Ulema Council (MUI), Halal Centers, and supporting factors on the success of halal product certification for MSMEs in West Nusa Tenggara (NTB). A quantitative approach with a survey design was used to collect data via Likert scale questionnaires distributed to 40 MSMEs undergoing or having completed halal certification. Research instruments were developed based on literature-derived indicators: MUI's role (socialization/education, ease of information access, credibility); Halal Center's role (technical assistance, training/workshops, ease of service access); and supporting factors (cost affordability, ease of information access, simplicity of the certification process). Multiple linear regression analysis using R software showed that all three independent variables significantly influenced halal certification success, with MUI's role being the dominant contributor. This research emphasizes the importance of synergy among supporting institutions and process improvements to enhance MSME competitiveness through halal certification, offering strategic recommendations for more efficient and applicable certification policies.